2014
DOI: 10.1016/j.spinee.2013.08.040
|View full text |Cite
|
Sign up to set email alerts
|

Finite element investigation of the effect of a bifid arch on loading of the vertebral isthmus

Abstract: The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription. Spondylolysis (SL) of the lower lumbar spine is frequently associated with spina bifida occulta (SBO). There has not been any study that has demonstrated biomechanical or genetic predispositions to explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A possible reason for the substantial variation in union rate between the reports is that there are multiple confounding factors that have a significant impact on bone union. Previous reports revealed several possible factors affecting bone union after conservative treatments for lumbar spondylolysis, including vertebral level [4], stage [4], contralateral condition [4], bilateral spondylolysis [5], and latent spina bifida [6,7]. Contralateral pseudarthrosis might be an inhibitory factor for bony union because new spondylolysis tends to occur when a bone defect occurs on the opposite side of the vertebral arch [8].…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for the substantial variation in union rate between the reports is that there are multiple confounding factors that have a significant impact on bone union. Previous reports revealed several possible factors affecting bone union after conservative treatments for lumbar spondylolysis, including vertebral level [4], stage [4], contralateral condition [4], bilateral spondylolysis [5], and latent spina bifida [6,7]. Contralateral pseudarthrosis might be an inhibitory factor for bony union because new spondylolysis tends to occur when a bone defect occurs on the opposite side of the vertebral arch [8].…”
Section: Introductionmentioning
confidence: 99%
“…Rarely, neurological manifestations can be observed in those who develop tethering of the spinal cord within the spinal canal. Also, SBO leads to inappropriate distribution of weight and attachment of muscles due to incomplete vertebral arch [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature have described a positive association between SBO and spondylolysis 14 16 . A recent finite element study showed a bifid arch in SBO and following laminectomy increases load across the isthmus, predisposing toward early fatigue fractures of the isthmus 17 . Similarly, SBO in the sacrum might affect the stress concentration on the sacral alae, predisposing toward stress fractures of the sacrum without repetitive stress.…”
Section: Discussionmentioning
confidence: 99%